2018
DOI: 10.1021/acs.jpca.8b06300
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational States and Nitrile Lifetimes of Cyanophenylalanine Isotopomers in Solution

Abstract: Nitrile lifetimes and the structure of the vibrational state space of four isotopomers of cyanophenylalanine in solution are calculated. While the frequency of the nitrile of the four isotopomers decreases in the order CN, CN, CN, and CN, the lifetime varies nonmonotonically with the change in frequency. The vibrational properties of the molecules that control the lifetime are examined. The specific resonances that contribute to the lifetime are tuned by isotopic substitution, and the magnitudes of the anharmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(52 citation statements)
references
References 60 publications
4
48
0
Order By: Relevance
“…This is due to alteration of the vibrational energy transfer rate from nitrile to other overtones of the low frequency modes. 20 This intramolecular energy dissipation phenomena for the CN mode has been observed in isotopically substituted nitriles. Here, the perturbing factor that changes the intramolecular relaxation is mass.…”
mentioning
confidence: 56%
See 4 more Smart Citations
“…This is due to alteration of the vibrational energy transfer rate from nitrile to other overtones of the low frequency modes. 20 This intramolecular energy dissipation phenomena for the CN mode has been observed in isotopically substituted nitriles. Here, the perturbing factor that changes the intramolecular relaxation is mass.…”
mentioning
confidence: 56%
“…Recent experimental and theoretical studies have shown that the nitrile frequency-shift changes the nitrile vibrational lifetime due to intramolecular coupling with other low frequency modes present in the molecule. This is due to alteration of the vibrational energy transfer rate from nitrile to other overtones of the low frequency modes . This intramolecular energy dissipation phenomena for the CN mode has been observed in isotopically substituted nitriles.…”
mentioning
confidence: 61%
See 3 more Smart Citations